神経線維腫症1型患者の口蓋に発生した巨大な神経線維腫の1例 - 比嘉, 努; 比嘉, 盛敏; 狩野, 岳史; 銘苅, 泰明; 新垣, 敬一; 仲間, 錠嗣 (日本口腔外科学会雑誌, 2021)
Neurofibromatosis type I (NF1) is a chromosomal dominant hereditary disease characterized by cafe-au-lait spots of the skin and multiple neurofibroma. Oral manifestation of NF1 is relatively infrequent. We report a rare case of huge neurofibroma arising in the palate, associated with NF1. A 39-year-old woman visited our department with the complaint of a painless mass in the hard palate. An elastic-soft swelling measuring 50 x 38 mm was found on the right palate. The tumor was excised under general anesthesia. Histopathological findings revealed neurofibroma. The tumor has not recurred, and the patient has made good progress.